Human Bone Marrow Mesenchymal Stromal Cell-Derived Extracellular Vesicles Promote Proliferation of Degenerated Nucleus Pulposus Cells and the Synthesis of Extracellular Matrix Through the SOX4/Wnt/β-Catenin Axis - Wang, Haoyu; Li, Fei; Ban, Wenrui; Zhang, Jing; Zhang, Guiqi (Frontiers in Physiology, 2021)
Objective: Intervertebral disk degeneration (IDD) is a major cause of pain in the back, neck, and radiculus. Mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) are therapeutic in musculoskeletal degenerative diseases such as IDD. This study explored the effect and functional mechanism of human bone MSCs (hBMSCs)-derived EVs in proliferation and apoptosis of degenerated nucleus pulposus cells (DNPCs) and extracellular matrix (ECM) synthesis. Methods: Extracellular vesicles were isolated from hBMSCs and identified. DNPCs were induced by TNF-α. EVs were incubated with DNPCs for 24h. Internalization of EVs by DNPCs, DNPCs proliferation, apoptosis, and expressions of ECM synthetic genes, degrading genes and miR-129-5p were assessed. Downstream target genes of miR-129-5p were predicted. Target relation between miR-129-5p and SRY-box transcription factor 4 (SOX4) was verified. DNPCs proliferation, apoptosis, and ECM synthesis were measured after treatment with EVs and miR-129-5p inhibitor or SOX4 overexpression. Expressions of SOX4 and Wnt/β-catenin pathway-related proteins were determined. Results: hBMSC-EVs promoted DNPCs proliferation, inhibited apoptosis, increased expressions of ECM synthetic genes, and reduced expressions of ECM degrading genes. hBMSC-EVs carried miR-129-5p into DNPCs. Silencing miR-129-5p in EVs partially inverted the effect of EVs on DNPCs proliferation and ECM synthesis. miR-129-5p targeted SOX4. SOX4 overexpression annulled the effect of EVs on DNPCs proliferation and ECM synthesis. Expressions of Wnt1 and β-catenin were decreased in EVs-treated DNPCs, while silencing miR-129-5p in EVs promoted expressions of Wnt1 and β-catenin. Conclusion: hBMSC-EVs promoted DNPCs proliferation and ECM synthesis by carrying miR-129-5p into DNPCs to target SOX4 and deactivating the Wnt/β-catenin axis.